A new reading of Tubero's De origine et incremento urbis Rhacusanae - Rezar, Vladimir (2012)
In 1790 the printing house of Dubrovnik brought to public a short historiographic treatise on Dubrovnik, written by Ludovicus Cervarius Tubero (1458–1527), a Benedictine monk and humanist. Ad hoc titled as De origine et incremento urbis Rhacusanae, the text was in fact an extended excerpt from the 5th book of Tubero’s master work, the Commentarii, and was made upon request of his patrons, Bernard Bánffy and Gregory Frankapan, who hosted him in 1509 in their episcopal see of Bács, Hungary. However, due to complex transmission circumstances of the text, up to our time the treatise appeared to circulate in several versions, both manuscript and printed, with significant content discrepancies. As the autograph original of the text was lost, it seemed worthwhile to try to establish a new critical edition of the treatise out of remaining textual testimonies. The attempt we expose here is to some extent unusual and philologically provocative, as an almost forgotten Italian translation of Tubero’s treatise (made in 1577 by Ragusan nobleman Simone Ragnina) is being used as a criterion by which the new critical edition of the text was formed. Namely, the Italian translation proved to be the most complete and trustworthy version of the treatise as far as the content is regarded, thus becoming a perfect key for eclectic insertion of Latin readings to the newly formed text, actually a cento made out of a collection of preserved variant Latin lections. As a result, the text established this way finally allows Tubero’s treatise to become an object of detailed philologic and litterary analysis, bringing forth some interesting facts that were so far unnoticed.
Keywords: Dubrovnik; Ludovik Crijević Tuberon